Fabrication of fabric-based flexible circuits via electron-beam radiation curing - ZHANG Maojiang; WANG Jinghua; WU Yanfu; DONG Chunlei; LIU Zhaowen; GAN Jie; CHEN Jianbing; WU Guozhong (Fushe yanjiu yu fushe gongyi xuebao)
This study focuses on the preparation of fabric-based flexible circuits using polyester fabric (PET) as a substrate via radiation curing and chemical copper plating methods. The microstructures, elemental distributions, durabilities, and stabilities of the flexible circuits were investigated. In this experiment, an industrial electron accelerator was utilized in conjunction with a steel plate "film" mold containing circuit structures to achieve selective irradiation by electron beams. Consequently, cured coating areas corresponding precisely to the designed circuit diagram (containing Ag/Fe3O4 catalyst) were formed on the fabric. Subsequently, metal layers were deposited in situ via chemical plating to construct fabric-based flexible circuits. Scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and X-ray diffraction (XRD) results demonstrated that the fabricated flexible circuit exhibited a well-defined structure and a highly crystalline conductive copper layer. During a bending test comprising 15 000 cycles, the resistance change rate of the fabric-based flexible circuit remained below 16%, whereas during a temperature variation test ranging from 15 ℃ to 55 ℃, it remained below 5%. These results suggest that the circuit exhibits exceptional durability and stability. The fabrication method for fabric-based flexible circuits presented herin offers novel insights into the development of smart textile products.